2010
DOI: 10.1007/s12192-009-0150-9
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock proteins and resistance to desiccation in congeneric land snails

Abstract: Land snails are subject to daily and seasonal variations in temperature and in water availability and depend on a range of behavioral and physiological adaptations for coping with problems of maintaining water, ionic, and thermal balance. Heat shock proteins (HSPs) are a multigene family of proteins whose expression is induced by a variety of stress agents. We used experimental desiccation to test whether adaptation to different habitats affects HSP expression in two closely related Sphincterochila snail speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 86 publications
4
48
0
1
Order By: Relevance
“…The authors concluded that Hsp70 does not have an essential function during aestivation in this species except for possible basal metabolic activities, and that the upregulation of HSPs in aestivating O. lacteal, as demonstrated by Brooks and Storey (Brooks and Storey, 1995), might be limited to the transition from an active to a depressed state, and might be not apparent in animals in the dormant state. This suggestion is confirmed by our studies in the land snail Sphincterochila, which provide a wider insight into the aestivation process, indicating the involvement of the HSP machinery in both experimental desiccation and as part of the natural annual cycle of activity and aestivation (Mizrahi et al, 2010) (present study). However, in contrast to experimental desiccation, in which desiccation induced the expression of most tested HSPs (Mizrahi et al, 2010), there was a general downregulation of HSP levels in aestivating compared with in active snails.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The authors concluded that Hsp70 does not have an essential function during aestivation in this species except for possible basal metabolic activities, and that the upregulation of HSPs in aestivating O. lacteal, as demonstrated by Brooks and Storey (Brooks and Storey, 1995), might be limited to the transition from an active to a depressed state, and might be not apparent in animals in the dormant state. This suggestion is confirmed by our studies in the land snail Sphincterochila, which provide a wider insight into the aestivation process, indicating the involvement of the HSP machinery in both experimental desiccation and as part of the natural annual cycle of activity and aestivation (Mizrahi et al, 2010) (present study). However, in contrast to experimental desiccation, in which desiccation induced the expression of most tested HSPs (Mizrahi et al, 2010), there was a general downregulation of HSP levels in aestivating compared with in active snails.…”
Section: Discussionsupporting
confidence: 89%
“…The authors concluded that, in Artemia, this protein might play the role of a metabolic regulator and/or a protective molecular chaperone during prolonged anoxia and other forms of stress. Our finding that sHSP responses were more pronounced in S. zonata compared with in S. cariosa is in agreement with our previous study demonstrating the stronger response of sHSPs to experimental desiccation in S. zonata snails (Mizrahi et al, 2010). However, it seems that the weaker induction of sHSPs in S. cariosa snails might reflect the higher standing stocks of sHSPs in this species that might suffice upon arousal.…”
Section: Hsps and Oxidative Stresssupporting
confidence: 92%
See 3 more Smart Citations